Trade Compliance Diagnosis in a Small Exporter Mexican Company - Arredondo-Hidalgo, María Guadalupe (Technium Social Sciences Journal, 2022)
An indicator of business competitiveness, at a global level, is the presence in international markets. It results in an extremely complex issue when the legal framework for this purpose is not known. Trade Compliance is defined as the observance of tariff and non-tariff barriers for the legal compliance of the considered country in the international planning of a company’s operations. The objective of this work was to carry out a Trade Compliance diagnosis in a small, Mexican company of the chemical industry for construction with 15 years in the market, through the revision of the procedures that the company performs for the development of international markets, based on the changes in the Mexican legislation to the year 2022. It is an applied case study with descriptive scope and non-experimental design. A verification guide was used to collect information based on the current legal framework, in addition to documentary information from secondary sources. The results show that the company complies with the guidelines of both Mexican regulations and global rules of origin. A continuous review of the import-export processes and their consequent adaptation to the International Treaties on International Trade is proposed.